Comparison of Early versus a Late Administration of Surfactant in Newborns with Respiratory Distress Syndrome (Sir Salimullah Medical College Journal, 2026)
Background: Respiratory distress syndrome (RDS) remains a leading cause of morbidity and mortality among premature newborns. Along with CPAP support, surfactant replacement therapy plays a critical role in determining outcomes. This study aimed to compare outcomes between early and late surfactant administration among preterm infants (